2008
DOI: 10.1590/s0100-204x2008000400015
|View full text |Cite
|
Sign up to set email alerts
|

Recobrimento de sementes de milho com ácidos húmicos e bactérias diazotróficas endofíticas

Abstract: O objetivo deste trabalho foi avaliar o efeito do recobrimento de sementes de milho com ácidos húmicos (AH), bactérias diazotróficas endofíticas e o uso em conjunto de AH e bactérias diazotróficas endofíticas, na estimulação do crescimento vegetal e na população de bactérias estabelecidas na planta hospedeira. A adição de AH, bactérias e o uso em conjunto estimularam o crescimento vegetal. Os AH utilizados no recobrimento de sementes de milho têm menor capacidade de estimular o crescimento radicular, em compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 5 publications
0
6
0
8
Order By: Relevance
“…Coating maize seed with DEB and HA was previously reported [29]. The germination was not affected by seed coating that promoted root growth enhancing 44% the root length in respect to control.…”
Section: Effects On Maizementioning
confidence: 65%
See 2 more Smart Citations
“…Coating maize seed with DEB and HA was previously reported [29]. The germination was not affected by seed coating that promoted root growth enhancing 44% the root length in respect to control.…”
Section: Effects On Maizementioning
confidence: 65%
“…H + -ATPase activation could also be mechanistically linked to the root hairs proliferation since it was demonstrated that cell growth depends on extracellular acidification in maize roots [44]. The DEB and HA-induced stimulation of the H + -ATPase activity [29] suggest that the modifications are not restricted to root architecture, but are also extended to major biochemical components. Indeed, the driving force for most nutrient uptake is the electrochemical gradient across the plasma membrane, which is primarily generated by the H + -ATPase.…”
Section: Physiological Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Assim, o recobrimento mostra-se como um meio de inoculação viável para bactérias diazotróficas endofíticas da espécie Herbaspirillum seropedicae (Z67), o que garante a sobrevivência dessas bactérias, no recobrimento, até a emissão das raízes pelas plantas, como observado por CONCEIÇÃO et al (2008).…”
unclassified
“…Conceição et al (2008) avaliaram o efeito da estimulação causada por bactérias diazotróficas endofíticas no desenvolvimento fisiológico de semente de milho utilizando Herbaspirillum seropedicae e não verificaram diferença significativa em relação à testemunha para germinação das sementes, corroborando com os dados da presente pesquisa. É oportuno ressaltar que a literatura não retrata sobre efeito positivo do grupo das bactérias diazotróficas endofíticas sobre a germinação de sementes de Zea mays L.…”
Section: Resultsunclassified